The Future of pastoralism : an introduction - Zinsstag, J. [et al] (2016)
Takes a broad view and provides a synthetic vision for the sustainable use of pastoral ecosystems, with innovative ideas for livelihoods, economic development, sustained ecosystem services and social and institutional development as the contect for animal and human health and wellbeing.